Assessment of serum sodium levels among the febrile seizures children in a tertiary care hospital - Penta, V Bharathi Tulasi; Lakkappa, Lakshmi (Indian Journal of Child Health, 2018)
Background: Pathophysiology of febrile seizures (FS) remains unclear. During acute febrile illness, mild disturbances of water and electrolyte balance occur frequently, particularly hyponatremia, which might predispose the child to convulsions. Objective: The objective of the study was to assess the serum sodium levels among the children with FS in a tertiary care hospital. Materials and Methods: A prospective case–control study was conducted at a tertiary care hospital in Bengaluru from January 2014 to October 2016. A total of 80 children with febrile convulsions were taken as cases and 80 children admitted for other causes weretaken as controls. Serum sodium levels were estimated and compared. Results: Mean age of cases was 20.09±11.63 months while that of the controls was 20.08±13.1 months. Among cases, 28.7% had hyponatremia, 66.2% had normal sodium levels, and 5% had hypernatremia. In controls, hyponatremia, normal sodium levels, and hypernatremia were seen in 6.2%, 82.5%, and 11.2% children, respectively. Conclusion: Incidence of hyponatremia was significantly high among the children with FS when compared to the controls. The mean serum sodium levels in cases were significantly lower than that in controls suggesting the role of relatively lowserum sodium levels in the occurrence of FS in children.